Phosphoinositides in insulin action on GLUT4 dynamics: not just PtdIns(3,4,5)P(3) - Shisheva, Assia (American Physiological Society, 2008)
Accumulated evidence over the last several years indicates that insulin regulates multiple steps in the overall translocation of GLUT4 vesicles to the fat/muscle cell surface, including formation of an intracellular storage pool of GLUT4 vesicles, its movement to the proximity of the cell surface, and the subsequent docking/fusion with the plasma membrane. Insulin-stimulated formation of phosphatidylinositol 3,4,5-trisphosphate [PtdIns(3,4,5)P(3); and in some cases, of its catabolite PtdIns(3,4)P(2)] plays a pivotal role in this process. PtdIns(3,4,5)P(3) is synthesized by the activated wortmannin-sensitive class IA phosphoinositide (PI) 3-kinase and controls the rate-limiting cell surface terminal stages of the GLUT4 journey. However, recent research is consistent with the conclusion that signals by each of the remaining five PIs, i.e., PtdIns(3)P, PtdIns(4)P, PtdIns(5)P, PtdIns(3,5)P(2), and PtdIns(4,5)P(2), may act in concert with that of PtdIns(3,4,5)P(3) in integrating the insulin receptor-issued signals with GLUT4 surface translocation and glucose transport activation. This review summarizes the experimental evidence supporting the complementary function of these PIs in insulin responsiveness of fat and muscle cells, with particular reference to mechanistic insights and functional significance in the regulation of overall GLUT4 vesicle dynamics.